(untitled) (Journal of Health Sciences, 2018)
Introduction: Unhealthy behavior such as neglecting to brush and floss, using tobacco and alcohol, and inadequate nutrition can adversely affect dental health. The frequency of dental visits is also of great importance in the early detection of different oral disorders. Our aim was to assess oral health behavior and attitudes among students of the 1st year of two health and non-health oriented studies of University of Sarajevo. Methods: We included 119 students of the 1st year of Faculty of Health Studies and 108 students of the 1st year of Faculty of Architecture of the University of Sarajevo. A self-administered questionnaire was used, comprising demographic data, data on oral hygiene habits, dental attendance pattern, a number of extracted teeth as well as problems with the appearance, comfort, and social life due to teeth problems. Results: Faculty of Architecture students significantly more often visit their dentist (χ2 = 24.174, df = 5, p = 0.00). Faculty of Health Studies students have significantly more extracted teeth (χ2 = 35.54, df = 4, p = 0.001). Dental health habits were significantly better at the students Faculty of Architecture (χ2 = 16.391, df = 2, p = 0.001). No significant difference between the groups about about avoiding encounters due to teeth and dentures problems. Conclusion: Oral health related attitudes may be better in students of non-health oriented studies, however, these results have to be confirmed by more investigations and larger studies.